“We’re in this together”: Changing intra-household decision making for more cooperative smallholder farming - Institute of Development Policy and Management; Lecoutere, Els; Jassogne, Laurence T.P. (2016)
Conceptualising smallholder farming households as collective action institutions, that make interrelated decisions about investment, resource use and allocation in a common household farm, may contribute to understanding widely observed uncooperative outcomes, such as yield gaps, gender gaps in productivity, suboptimal or Pareto inefficient sustainable intensification and climate change adaptation. We examine the relation between participatory intra-household decision making – as a set of ‘rules of the game’ that reduces information and bargaining power asymmetries – and cooperative, i.e. more efficient, sustainable and equitable, outcomes in smallholder coffee farming households in Uganda. We find experimental evidence that participatory decision making is positively related to investments in the common household farm. Consumption behaviour however is not fairer nor more sustainable. Participatory decision making is associated with more cooperative actual outcomes such as greater investment in sustainable intensification, consideration of women’s interests, fairer reproductive intra-household labour division, more balanced control over cash crop income and improved livelihoods.